Nilai-Nilai Pendidikan Agama Hindu Yang Terkandung Dalam Geguritan Lubdaka - Anak Agung Istri Dwi Wulandari; I Wayan Mandra; Gek Diah Desi Sentana (Jayapangus Press, 2019)
Geguritan Lubdaka is one of the classic literary works containing a lot of moral knowledge and religion. The teachings in Geguritan Lubdaka provide motivation in improving the spiritual quality of human beings. Judging from its contents as a whole Geguritan Lubdaka contains many religious teachings as well as religiou ceremonies (rituals) and speech (advice). The problem will be discussed, among others, (1) How is the structure of Geguritan Lubdaka, as one of the traditional literary works of Bali, (2) What is the function of Geguritan Lubdaka when associated with the social and religious (religious) environment ?, (3) Values What kind of Hindu Religious Education is contained in Geguritan Lubdaka ?. Theories used to analyze problems are: structuralism theory, functional theory, and value theory. The method used is: Type of Research and research approach, Data Types and Data Sources, Data Collection Techniques which include Observation, Interview, Library Studies and Documentation, Data Analysis include descriptive analysis methods and hermeneutic analysis methods, and the last method of data analysis. The function of Geguritan Lubdaka in social environment as the media of individual and group entertainer, giving message and meaning so that we can control ourselves from negative things, indirectly Geguritan Lubdaka also can be used as education media in teaching Dharma Gita especially Hindu religion, and can unite individual into one group (Sekaa Santi). While the function of divinity or religion can be seen through the figures of the gods that are found in Geguritan Lubdaka, such as Lord Shiva and God Yama. Furthermore, based on the analysis of the structure can be disclosed the values ​​of Hindu religious education contained in Geguritan Lubdaka namely the value of tattwa education (philosophy of Religion), the value of moral education (ethics) and the value of education ceremony. The point between literature and religion has a very close relationship and has an important role in supporting religious activities, and does not leave its limitations. So philosophy, ethics and ceremony are the basic concepts of Hinduism that have an important role in the Geguritan Lubdaka.